THE BAND OF ABDUL QAHHAR MUDZAKKAR: Biographical Sketch of Rebelious Leaders of Islamic State-Indonesian Islamic Army (DI/TII) of Sulawesi (JOURNAL OF INDONESIAN ISLAM, 2014)
The rebellious movement of Islamic State-Indonesian Islamic Army (DI/TII) began from dissatisfaction towards the secular state of newly independent Indonesia. Abd. Qahhar Mudzakkar, the leader of DI/TII in Sulawesi and his followers revolted against the government, and subsequently formed their own Islamic government. Since Qahhar graduated from Muhammadiyah school, his theological basis in his cause to establishing an Islamc state is very prevalent. He believed that his Islamic state is to uphold the truth and to defend the religion of Allah. Thus whoever opposed his DI/TII movement would be considered infidel simply because of favoring or supporting the Indonesian government they considered secular and communist. His followers and supporters were preachers and clerics, who helped Qahhar by carrying out specific functions and positions in his Islamic state. In addition, those people played an important role in getting recognition and acceptance of Sulawesi muslim society for Islamic state campaign launched by Abdul Qahhar Mudzakkar. Without their involvement, DI/TII would never had been so popular among muslim community in Sulawesi.